Gubernativas e insuplicables. Competencias de jurisdicción entre Monarquía judicial y Estado administrativo (1768-1845) - Martínez-Pérez, Fernando (Historia del Derecho, 2022)
Giving, taking away and declaring jurisdiction was one of the most important royalties of the monarch in the Ancien Régime and one of the most difficult to delegate. It was no less so in a world in which any act of power involving the alteration of the legal situations obtained by the unequal subjects that composed it required knowledge of the cause, and in which sovereignty was expressed in the capacity to judge others without being judged. For this reason, the examination of the methods and practice followed for the determination of jurisdictional competences and disputes becomes a privileged observatory for studying the crisis of the judicial Monarchy and its replacement by an administrative State in a Spain that in 1768 was bicontinental and in 1845 peninsular and little more than Antillean. This book gives an account of all the methods which, without being able to attack the root of the problem consisting of the multiplicity of privileged jurisdictions, were tried to reduce its consequences in a period framed by the expansion of these jurisdictions and the birth of the contentious-administrative jurisdiction. This work of constitutional history does not lose sight of the political value of the power to determine competences first between courts and then between powers and authorities, and thus to "supplement the constitution", and notes how, for almost a century, systems for resolving competences that obeyed the character of a "trial between judges" coexisted in tension with others in which the aim was to unilaterally decide disputes by invoking the economic and governmental dimension of the power of the princes. But this period also saw a shift from the consideration of jurisdictional competence as a necessary evil, a last resort to be resorted to in order to maintain harmony between authorities, to the normalisation of the conflict in a new French-style taxonomy of "jurisdiction" and "attributions".